Interactive/automated method to count bacterial colonies - Monteiro, Fernando C. (2018)
The number of colonies in a culture is counted to calculate the concentration of bacteria in the original broth; however, manual counting can be tedious, time-consuming and imprecise. Automation of colony counting has been of increasing interest for many decades, and these methods have been shown to be more consistent than manual counting. Significant limitations of many algorithms used in automated systems are their inability to recognize overlapping colonies as distinct and to count colonies on the plate boundary. This study proposes an interactive semi-automated counting system and a fully automated counting system using image processing methods which overcomes these problems. The proposed systems are capable to reduce the manpower and time required for counting colonies while taking account colonies both around the central area and boundary areas of a Petri dish.